Variability in daily or weekly working hours and self-reported mental health problems in Korea, Korean working condition survey, 2017 - Hye-Eun Lee; Myoung-Hee Kim; Min Choi; Hyoung-Ryoul Kim; Ichiro Kawachi (BMC, 2021)
Abstract Background Working hour regulation in Korea is being revised to allow increasing variability in number of working hours. We sought to investigate the association between variability in the number of daily or weekly working hours with or without long working hours (> 52 h/w) and mental health among South Korean workers. Methods We used data from 28,345 full-time, non-shift employed workers working more than 30 h per week participating in the Korean Working Condition Survey in 2017. We defined six groups according to variability in daily or weekly working hours (same number vs different number) and weekly working hours (31-40, 41-52, > 52 h per week). Odds ratios (ORs) and confidence intervals (CIs) for self-reported depressive symptoms and anxiety were calculated using workers with same number of working hours/31-40 h per week as the reference. Results Variability in number of work hours every day or week combined with > 52 working hours per week showed the highest risk of depressive symptoms (OR = 5.13, 95% CI 3.25-8.11) and anxiety (OR = 3.75, 95% CI 2.39-5.88) compared to the reference group, controlling for age, sex, education, occupation, industry, salary, workers' choice of working hours and overtime payment. Workers working ≤52 h/w were adversely impacted by variable working hours as well. Conclusions Variable daily or weekly working hours were associated with poorer self-reported depressive and anxiety symptoms in Korea, among full-time and non-shift workers. Reform of the Korean Labor Standards Act warrants consideration.